Penampilan Kelinci Persilangan Lepas Sapih yang Mendapat Ransum dengan Beberapa Tingkat Penggunaan Ampas Teh - L Khotijah; R G Pratas; E Fiberty (Faculty of Animal Science, Bogor Agricultural University, 2004)
Tea waste is by-product of tea manufacturer that is potential as an alternative of protein source. Twenty male cross-breed weanling rabbits were used to investigate the optimum utilization of tea waste in ration of rabbit. Completely randomized design was used with four treatments and five replications. The levels of tea waste in pellet rations as the treatment consisted of 0% (AT0), 10% (AT10), 20% (AT20), and 30% (AT30) of dry matter. The dry matter intake, average daily gain (AVG), ration conversion, mortality, and economical value were measured in this experiment. The result showed that the treatments did not significantly affect dry matter intake, average daily gain, and ration conversion. The mortality was 0 percent and the profit increased in ration containing tea waste. It was concluded that tea waste could support good performance of the rabbits and it could be used as an alternative of protein sources until 30% in ration. Key words: rabbit, tea waste, protein sources